(untitled) (Periodicals of Engineering and Natural Sciences, 2021)
Baghdad City suffers from a continual horizontal urban expansion causing a multitude of urban problems that limit sustainable development. This paper presents an applied study to monitor the stages of urban sprawl of the Al-Zawra area, located on the outskirts of Baghdad City. This study is conducted by following the urban sprawl changes during the period between 2000 and 2020. This study assumes the adoption of the control strategy called urban inverse densification according to the principles of sustainable urban development. The study used the descriptive method and the statistical analytical approach to data extracted from satellite images and topographic maps collected from various sources. The results showed that the population growth distribution indicator in the sprawl phenomenon (Ps) reached 80.71 %, compared to the densification phenomenon (Pd) 13.62 %. While the gross per capita urban land indicator in the sprawl (Ds) reached 19.29 %, compared to densification (Dd) 86.38 %. Therefore, there is an inverse relationship between the population and density indicators and their effect on urban sprawl and urban densification. The results showed the efficacy of an analytical statistical model for rehabilitating urban sprawl areas and reducing pressure on the outskirts of big cities through sustainable inverse densification.